2012
DOI: 10.1002/elps.201200001
|View full text |Cite
|
Sign up to set email alerts
|

A proteome signature for intrauterine growth restriction derived from multifactorial analysis of mass spectrometry‐based cord blood serum profiling

Abstract: Intrauterine growth restriction (IUGR) is defined as a condition in which the fetus does not reach its genetically given growth potential, resulting in low birth weight. IUGR is an important cause of perinatal morbidity and mortality, thus contributing substantially to medically indicated preterm birth in order to prevent fetal death. We subjected umbilical cord blood serum samples either belonging to the IUGR group (n = 15) or to the control group (n = 15) to fractionation by affinity chromatography using a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 55 publications
1
45
0
Order By: Relevance
“…Subsequently, these authors reported that MS profiling is confirmatory to clinical surveillance with the potential to identify neonates with IUGR postnatally [27]. As far as we know, the present study is the first to assess the changes in serum proteome of IUGR neonates stratified by their GA, in venous blood samples drawn at 1, 7 and 30 days after birth, not in umbilical cord blood as previously made in previous studies in human neonates [24][25][26][27]. Sera from each GA group were pooled, so that each neonate contributed an equal amount of protein to the mixture before 2-DE analysis.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Subsequently, these authors reported that MS profiling is confirmatory to clinical surveillance with the potential to identify neonates with IUGR postnatally [27]. As far as we know, the present study is the first to assess the changes in serum proteome of IUGR neonates stratified by their GA, in venous blood samples drawn at 1, 7 and 30 days after birth, not in umbilical cord blood as previously made in previous studies in human neonates [24][25][26][27]. Sera from each GA group were pooled, so that each neonate contributed an equal amount of protein to the mixture before 2-DE analysis.…”
Section: Discussionmentioning
confidence: 64%
“…Cord blood alterations toward an atherogenic phenotype were assumed to underlay the predisposition of IUGRs for cardiovascular diseases [34]. Thus, in umbilical cord blood sera of 15 IUGR and 15 AGA, the six best ion signals obtained by MALDI-TOF profiling were considered to represent the IUGR proteome signature, also suggesting apolipoprotein C-III 0 as a potential key marker [26]. Since they focused on the atherogenic phenotype secondary to IUGR, a Protein Profiling Kit MB-HIC8 (Bruker) based on hydrophobic interactions was used to enrich the serum proteins from umbilical cord blood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations